Great world religions Christianity - Johnson, Luke Timothy (Great courses, 2003)
Provides an overview of Christianity, the world's largest religion, and discusses why, in addition to being vast and popular, it is also extremely complex and often highly contradictory. Explains why the central figures, elements, and creeds of Christianity are hard to fathom yet give Christianity its distinctive character. Covers topics such as Christianity's birth and expansion across the Mediterranean world, the development of its doctrine, its assertion that Jesus was both a man and God, its transformation upon becoming Rome's imperial religion, its many and deep connections to Western culture, and the tensions in Christianity today.